Bulky Pulmonary Mucosa-Associated Lymphoid Tissue Lymphoma Treated with Yttrium-90 Ibritumomab Tiuxetan. (26th November 2013) - Tamura, Shinobu; Ikeda, Tokuji; Kurihara, Toshio; Kakuno, Yoshiteru; Nasu, Hideki; Nakano, Yoshio; Oshima, Koichi; Fujimoto, Tokuzo
Abstract : An 84-year-old woman was admitted to our hospital with nonproductive cough and dyspnea on exertion. Computed tomography (CT) scan revealed extensive consolidation in the right lung. She was diagnosed with pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma using CT-guided lung biopsy. Her pulmonary images and respiratory symptoms did not improve two months after receiving 4 cycles of rituximab weekly; therefore, yttrium-90 ibritumomab tiuxetan was chosen as salvage therapy. The abnormal shadow on her pulmonary images was significantly reduced two months later, and she had no symptoms without nonhematological toxicities. She has had no progression for 18 months. Furthermore, radiation pneumonitis has not also been observed. We herein reported bulky pulmonary MALT lymphoma treated with yttrium-90 ibritumomab tiuxetan.